Perlindungan Hukum Terhadap Tanah Adat Suku Bugis/Tolotang Di Kabupaten Sidenreng Rappang - Heril Heril; Andi Suriyaman M Pide; Sri Susyanti Nur (Fakultas Hukum Universitas Sultan Ageng Tirtayasa, 2022)
The Towani Tolotang people still retain their beliefs from their ancestors, even though living in modern times today they are able to prove their existence by consistently maintaining their religious and cultural activities. Land is very important for the Towani Tolotang people because the land is not only a place to live and grow crops, but as a place to carry out religious or customary activities carried out throughout their existence. This research will examine the legal protection of land from Towani Tolotang in Sidenreng Rappang Regency. This type of research is empirical legal research, data sources are primary and secondary data and are analyzed descriptively. The results of the study found that preventive legal protection of towani Tolotang customary land until now has not existed, either the land registration or the recognition/regional regulations that protect the Towani Tolotang customary land. However, physical control of the land has been carried out from hundreds of years by their ancestors and there is recognition by the surrounding community of the control. The land that has strong legal evidence in this case the land certificate is the lands of the Towani Tolotang community which are used individually. The second type of legal protection is repressive, although the Towani Tolotang and Islamic people coexist in Amparita Lama (Amparita Village, Toddang Pulu Village, Arateng Village and Baula Village) they have different problem solving. In the Towani Tolotang society those who have disputes such as land can settle in Uwa' or Uwatta' which is the highest class among them. It was the fatwa of Uwa' or Uwatta' that was made legal by the Towani Tolotang people. Meanwhile, when the community is both Islamic or Islamic with Towani Tolotang, the dispute will be resolved in the village of the community or even can go to court in Sidenreng Rappang Regency.